Correlation between Blood Vitamin D Levels and Lipid Profiles in Post-Ischemic Stroke Patients - Jaeri, Santoso; Retnaningsih, Retnaningsih; Husni, Amin; Maharani, Nani; Anjani, Gemala (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Dyslipidemia and vitamin D deficiency are the predisposing factors for stroke. It is also established that vitamin D contributes to cholesterol metabolisms. Unfortunately, there is no evidence regarding the correlation between blood vitamin D levels and lipid profiles in patients with post-ischemic stroke. Herewith, the authors determine the correlation between blood vitamin D levels and lipid profiles among patients with post-ischemic stroke. A cross-sectional approach among 40 patients with post-ischemic stroke was obtained consecutively. Demographic characteristics, as well as the history of other diseases and 24 24-hour recall diet, were recorded. Then, the measurement of blood vitamin D levels and lipid profiles, such as total, LDL, HDL cholesterol, and triglyceride levels, were performed. Their correlations were determined using the Spearman correlation test. Among 40 subjects, no significant correlation was revealed between blood vitamin D levels and the serum total, LDL, HDL cholesterol, and triglycerides levels (p=0.898, 0.560, 0.361, and 0.622 respectively, and r=0.021, -0.095, 0.080, and 0.080 respectively). To summarize, there is no significant correlation between blood vitamin D levels and all lipid profiles in patients with post-ischemic stroke.